Association between metabolic and hormonal profile, proinflammatory cytokines in saliva and gingival health in adolescent females with polycystic ovary syndrome - Natalia Wendland; Justyna Opydo-Szymaczek; Dorota Formanowicz; Anna Blacha; Grażyna Jarząbek-Bielecka; Małgorzata Mizgier (BMC, 2021)
Abstract Background Research studies indicate that polycystic ovary syndrome (PCOS) may increase susceptibility to periodontal disease. The mechanisms that link both conditions are not entirely understood. Thus, the study aimed to investigate the impact of hormonal and metabolic disturbances on the gingival health and salivary levels of tumor necrosis factor (TNF-α), interleukin 1β (IL1-β), and interleukin 6 (IL-6) in adolescent girls with PCOS. Methods Thirty-one patients with PCOS and twenty-eight healthy age-mates (as the control group) were enrolled in the study. Individuals with PCOS underwent blood tests for the determination of hormonal and metabolic parameters. Saliva samples were collected to measure salivary testosterone and proinflammatory cytokines in both studied groups. Calibrated dentist assessed oral hygiene and gingival health of all subjects. Results Salivary testosterone was significantly higher in the study group (p = 0.0007). The groups did not differ significantly concerning periodontal parameters. Patients with PCOS revealed higher levels of salivary cytokines (p < 0.0001). Gingival index (GI) and the percentage of sites bleeding upon probing (BOP%) were positively correlated with the plaque index (PI) in both groups (rs ≥ 0.60, p < 0.001), and negatively correlated with salivary testosterone level in the PCOS group (rs = − 0.44, p = 0.0138 and rs = − 0.37, p = 0.0424, respectively). BOP% was also positively correlated with body mass index (BMI) in the control group (rs = 0.40, p = 0.0368) and index of insulin resistance (HOMA-IR) in the study group (rs = 0.48, p = 0.0068). Salivary testosterone was positively correlated with TNF-α in the control group (rs = 0.41, p = 0.0321), while in the study group, total testosterone (TT) was positively correlated with IL-6 (rs = 0.37, p = 0.0400) and free androgen index (FAI) with TNF-α (rs = 0.36, p = 0.0491). Conclusions Gingival health of the examined population was associated primarily with oral hygiene and, to a lesser extent, with the hormonal and metabolic profile. Despite similar periodontal parameters in the both studied groups, patients with PCOS revealed significantly higher levels of proinflammatory cytokines in saliva, which might be the manifestation of the systemic low-grade inflammation associated with PCOS.